Glucose-mediated inhibition of calcium-activated potassium channels limits α-cell calcium influx and glucagon secretion - Dickerson, Matthew T; Dadi, Prasanna K; Altman, Molly K; Verlage, Kenneth R; Thorson, Ariel S; Jordan, Kelli L; Vierra, Nicholas C; Amarnath, Gautami; Jacobson, David A (American journal of physiology: endocrinology and metabolism, 2019)
Pancreatic α-cells exhibit oscillations in cytosolic Ca (Ca ), which control pulsatile glucagon (GCG) secretion. However, the mechanisms that modulate α-cell Ca oscillations have not been elucidated. As β-cell Ca oscillations are regulated in part by Ca -activated K (K ) currents, this work investigated the role of K in α-cell Ca handling and GCG secretion. α-Cells displayed K currents that were dependent on Ca influx through L- and P/Q-type voltage-dependent Ca channels (VDCCs) as well as Ca released from endoplasmic reticulum stores. α-Cell K was decreased by small-conductance Ca -activated K (SK) channel inhibitors apamin and UCL 1684, large-conductance Ca -activated K (BK) channel inhibitor iberiotoxin (IbTx), and intermediate-conductance Ca -activated K (IK) channel inhibitor TRAM 34. Moreover, partial inhibition of α-cell K with apamin depolarized membrane potential ( V ) (3.8 ± 0.7 mV) and reduced action potential (AP) amplitude (10.4 ± 1.9 mV). Although apamin transiently increased Ca influx into α-cells at low glucose (42.9 ± 10.6%), sustained SK (38.5 ± 10.4%) or BK channel inhibition (31.0 ± 11.7%) decreased α-cell Ca influx. Total α-cell Ca was similarly reduced (28.3 ± 11.1%) following prolonged treatment with high glucose, but it was not decreased further by SK or BK channel inhibition. Consistent with reduced α-cell Ca following prolonged K inhibition, apamin decreased GCG secretion from mouse (20.4 ± 4.2%) and human (27.7 ± 13.1%) islets at low glucose. These data demonstrate that K activation provides a hyperpolarizing influence on α-cell V that sustains Ca entry during hypoglycemic conditions, presumably by preventing voltage-dependent inactivation of P/Q-type VDCCs. Thus, when α-cell Ca is elevated during secretagogue stimulation, K activation helps to preserve GCG secretion.